0755 Pitolisant (Wakix) is an Effective Anti-Cataplexy Agent in Narcolepsy Type 1. (27th May 2020) - Meskill, G J
Abstract: Introduction: Harmony Biosciences initiated the Pitolisant Expanded Access Clinical Evaluation (PEACE) program to allow treatment with pitolisant in adult patients with narcolepsy while pitolisant was an investigational medication in the United States. Starting in March 2019, Comprehensive Sleep Medicine Associates (CSMA) offered enrollment to patients who met the inclusion/exclusion criteria and who were deemed appropriate based on clinical judgment. All patients who enrolled were taking at least one standard-of-care agent for narcolepsy at enrollment. Many of the enrolled patients had refractory/challenging cases of narcolepsy. On August 14, 2019, Wakix received FDA approval for the treatment of excessive daytime sleepiness in adult patients with narcolepsy, which contrasts with the European label that states that Wakix is indicated for the treatment of narcolepsy in adults with or without cataplexy. Methods: CSMA enrolled 21 patients in the PEACE program. The charts for all 10 narcolepsy type 1 (NT1) patients were reviewed. The 2 patients who did not have follow up after starting pitolisant were excluded. Results: Of the 8 NT1 patients who had at least one follow up visit after initiating pitolisant, 6 reported substantial improvement or complete resolution of cataplexy compared to baseline. For example, one patient's wife stated, "I forgot my husband was funny because he would avoid telling jokes until he started pitolisant." Another stated, "I have not had an episode of cataplexy since starting pitolisant." 5 of these patients were taking an anti-cataplectic agent at the time of starting pitolisant (sodium oxybate 3, venlafaxine 2). Conclusion: While a relatively small sample size, these results demonstrate that in a "real world" uncontrolled population of refractory/challenging NT1 patients, pitolisant is an effective anti-cataplectic agent. As there are relatively few treatment options for NT1, clinicians should consider use of pitolisant for patients with cataplexy, and further consideration for adding an indication for pitolisant to treat cataplexy is warranted. Support: Harmony Biosciences (PEACE trial)